Effectiveness of Beauveria bassiana Powder as Larvacide to Aedes aegypti Linnaeus, 1762 Larvae - Hariani, Nova; Wulandari, Eka; Dharma, Bodhi (Jurnal ILMU DASAR, 2018)
Study of effectiveness of Beauveria bassiana Powder as Larvacide to Aedes aegypti larvae was conducted on September 2016 to May 2017 in Ecologi and Systematics Animal Laboratory, Faculty of Mathematics and Natural Sciences, University of Mulawarman. This study aimed to determine the effect of Beauveria bassiana powder with use flour rice media on differents concentration as larvacide to mortality of larvae Aedes aegypti. Stages of study include arranged experimental design (Completely Randomized Design) with concentration of 0%, 0.125%, 0.25%. 0.5% and 0.75%, taking sample, rearing third instar larvae of Aedes aegypti and application Beauveria bassiana powder in 48 hours observation. The mortality value of larvae willbe presented on percentage tabel and graph. The result showed, this product is capable of killing larvae for 48 hours with the percentage mortality 0%, 10%, 28%, 70% and 80% in each concentration. Mortality of larvae is influenced by concentration and period of exposure. Increased of product concentration that given and period of exposure can effected increased of mortality percentage. Keywords: mortality, Beauveria bassiana powder, Aedes aegypti larvae